Antimicrobial susceptibility patterns of Escherichia coli from various clinical sources - Waleed A. Al Qahtani; Mohamed S. Zaghlol; Yazeed Ali Mohammed Qasem; Mohsen M. Mashi; Ahmed A. Daghriri; Yahya kubaysi; Hisham N. Hakami; Alallah F. Khawaji; Nabil T. Hakami; Mohammed A. Jeraiby; Hassan N. Moafa; Mohammed Ezzi; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract